EXTENT OF USE OF THE NOVEL FABACEOUS HOST CENTROSEMA MOLLE BY HENOSEPILACHNA VIGINTIOCTOPUNCTATA (COLEOPTERA: COCCINELLIDAE) IN NUSA TENGGARA, INDONESIA - Fujiyama, Naoyuki; Ueno, Hideki; Kahono, Sih; Hartini, Sri; Matsubayashi, Kei W; Kikuta, Shogo; Katakura, Haruo (Treubia, 2014)
-